Association of Genetic Polymorphisms in DC-SIGN, Toll-Like Receptor 3, and Tumor Necrosis Factor α Genes and the Lewis-Negative Phenotype With Chikungunya Infection and Disease in Nicaragua. (27th June 2020) - Bucardo, Filemón; Reyes, Yaoska; Morales, Marlen; Briceño, Rafaela; González, Fredman; Lundkvist, Åke; Svensson, Lennart; Nordgren, Johan
Abstract: Background: Chikungunya infections range from subclinical infection to debilitating arthralgia and to chronic inflammatory rheumatism. Tumor necrosis factor (TNF) α, DC-SIGN (dendritic cell–specific intercellular adhesion molecule 3–grabbing nonintegrin), Toll-like receptor (TLR) 3, and blood groups have been directly or indirectly implicated in the susceptibility and pathogenesis of chikungunya. Methods: To test the hypothesis that polymorphisms in genes coding for these molecules determine clinical outcomes of chikungunya infection, a retrospective case-control study was performed in León, Nicaragua. The study included 132 case patients and 132 controls, matched for age, sex and neighborhood. Case patients had clinical symptoms of chikungunya, which was diagnosed by means of polymerase chain reaction. Controls were individuals not reporting abrupt presentation of clinical chikungunya-like symptoms. Polymorphisms were identified by TaqMan single-nucleotide polymorphism genotyping assays. Results: After adjustment for sociodemographic risk factors, chikungunya disease was associated with polymorphism in DC-SIGN and TLR3 genes (odds ratios, 5.2 and 3.3, respectively), and TNF-α with reduced persistent joint pain (0.24). Persistent joint pain was also associated with age, female sex and other comorbid conditions. Most interestingly, the Lewis-negative phenotype was strongly associated with both symptomatic chikungunya and immunoglobulin G seropositivity (odds ratios, 2.7, and 3.3, respectively). Conclusion: This study identified polymorphisms in DC-SIGN, TLR3, and TNF-α genes as well as Lewis-negative phenotype as risk factors for chikungunya infection and disease progression. Abstract : Host genetic factors influence susceptibility to chikungunya infection and disease progression. Polymorphisms in DC-SIGN, Toll-like receptor 3, and Lewis blood group genes were associated with disease susceptibility, and polymorphism in tumor necrosis factor α gene with joint pain persistence.